Strength Properties of 17Mn1Si Steel Welded Joints Subjected to Pulsed Mechanical-Electrophysical Treatment - Smirnova A. S.; Vlasov I. V.; Stankevich R. V.; Yakovlev A. V.; Pochivalov Yu. I.; Valuev D. V. Denis Viktorovich; Panin S. V. Sergey Viktorovich (2018, 2018)
Title screen